Management Of Funding Products And Financing Products In Fulfilling Liquidity At Pt. Bank Syariah Mandiri Branch Sengkang South Sulawesi - Hijriani, Zhulfi; Trimulato, Trimulato; Nuringsih, Nuringsih; Lismawati, Lismawati (el-Amwal, 2024)
Maintaining the health of Bank Syariah Mandiri Sengkang Branch, among other things, is carried out while maintaining its liquidity so that the bank can fulfill obligations to parties who withdraw or withdraw their deposit funds at any time. This study discusses that liquidity is influenced by two factors, namely fundraising and channeling of funds so that Bank Syariah Mandiri Branch Sengkang South Sulawesi manages funding products and financing products as well as possible. This research aims to find out how to manage funding products and financing products at PT. Bank Syariah Mandiri Branch Sengkang and to find out the management of funding products and financing products to meet liquidity at PT. Bank Syariah Mandiri Branch Sengkang. This research is a type of research with qualitative methods. The source of the data used in this research is the primary data approach through interviews, observation, and communication with parties related to PT. Bank Syariah Mandiri Branch Sengkang. The data analysis technique used in this study is descriptive analysis, namely data analysis on the types of funding and financing products and managing them to meet bank liquidity. After going through the analysis process, it is obtained that the funding product has been managed properly which can be seen in the number of third-party funds or fund collectors stored. Financing products at Bank Syariah Mandiri Sengkang Branch have also been good, seen from the lack of bad loans and being able to limit the taking of financing its liquidity can also be said to be productive because it can fulfill its financial obligations on time.